2017
DOI: 10.1093/pubmed/fdx162
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating for oral health in support of vulnerable older people: co-production of oral health training in care homes

Abstract: This study suggests that co-production of an oral care training package for care home staff, is possible and welcome, but challenging in this complex and changing environment. Further work is needed to explore the feasibility, sustainability and impact of doing so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…Their stories informed the development of culturally sensitive oral health promotion involving members of the community as actors in an audio‐visual tool 57 . Co‐production has challenges, however, which could be the reason why there are few examples of co‐produced interventions addressing oral health inequalities 37,61,62 . Barriers include dominant expert‐based research processes, 54 differing priorities, 63 and a lack of knowledge and understanding about what co‐production means 64,65 …”
Section: What Do We Know About the Application Of Intersectionality Imentioning
confidence: 99%
“…Their stories informed the development of culturally sensitive oral health promotion involving members of the community as actors in an audio‐visual tool 57 . Co‐production has challenges, however, which could be the reason why there are few examples of co‐produced interventions addressing oral health inequalities 37,61,62 . Barriers include dominant expert‐based research processes, 54 differing priorities, 63 and a lack of knowledge and understanding about what co‐production means 64,65 …”
Section: What Do We Know About the Application Of Intersectionality Imentioning
confidence: 99%
“…Example : Measure unconscious bias among dental students and providers and models its effects on treatment decision making and care delivery, particularly in response to patient subjective reports such as pain or behavioral intervention adherence, and standard of care [21–24]…”
Section: Commentarymentioning
confidence: 99%
“…Table 1 describes additional research questions related to oral health service delivery, patient‐reported and population‐level outcomes, and workforce studies that warrant inquiry using our proposed lens to center racism and consider racism across different levels. Scholars may also build on the limited‐but‐developing scholarship of racism and oral health outcomes to address areas including: Procedure decision studies that assess how implicit bias and racism affects dental team members clinical decision‐making and subsequent patient‐ and population‐level health outcomes, for example, the management of self‐reported oral pain [21,22]; The effects of patient‐provider discordance or concordance on clinical decisions and outcomes, for example, self‐identification through an intersectionality framework [51]. Community studies that document how community members' experiences with racism, discrimination, and prejudice in everyday and health care settings impact decisions to utilize dental services [23,28]; Pedagogical studies to develop and evaluate the impacts of antiracist provider education on dental practice [52]; Workforce studies to identify and strengthen pathways to dental careers among minoritized students and to understand provider support for interventions that advance equity in oral health service delivery, for example, accepting patients with Medicaid dental benefits and supporting autonomy in oral health prevention specialists' practice; Policy studies to determine the relationships between structural racism and oral health policy interventions, for example, municipal water quality and fluoridation in historically redlined or minoritized neighborhoods [29,53]; and Intervention studies that address structural racism to improve patient outcomes and access to care. …”
Section: Commentarymentioning
confidence: 99%
“…Having agreed the risk assessment parameters, the existing care homes programme was adapted with a preventative focus based on 'proportionate universalism' 13 : Universal actions were offered to all care home residents, and those deemed at higher risk had additional preventative measures put in place. The universal component, of the oral health prevention programme, centred on oral care training for staff and development of an oral care policy for the care home 14 ; the targeted component, offered to those at elevated risk of oral diseases, comprised of additional support with oral hygiene practices and prescription of supplementary fluoride in the form of varnish and/or high fluoride toothpaste.…”
Section: A Working Group Includingmentioning
confidence: 99%